2021
DOI: 10.3390/coatings11020249
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of Electrospun Poly(acrylonitrile) Nanofibers on Conductive and Isolating Foil Substrates

Abstract: Electrospinning can be used to prepare nanofibers from various polymers and polymer blends. The adhesion of nanofibers to the substrates on which they are electrospun varies greatly with the substrate material and structure. In some cases, good adhesion is desired to produce sandwich structures by electrospinning one material directly onto another. This is the case, e.g., with dye-sensitized solar cells (DSSCs). While both pure foil DSSCs and pure electrospun DSSCs have been examined, a combination of both tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
(43 reference statements)
0
10
0
Order By: Relevance
“…This is why research groups use it. Especially, many researchers are interested in environmentally friendly electrospinning, in which low-toxic solvents and biopolymers are used to produce nanofibers [ 51 , 52 ].…”
Section: Production Methods Of Nanofibers Matsmentioning
confidence: 99%
“…This is why research groups use it. Especially, many researchers are interested in environmentally friendly electrospinning, in which low-toxic solvents and biopolymers are used to produce nanofibers [ 51 , 52 ].…”
Section: Production Methods Of Nanofibers Matsmentioning
confidence: 99%
“…Electrospinning is a well-known simple, productive process for producing highly functional fibers in the micro-and nanometer range [84]. The advantages of nanofibers include easy and low-cost manufacturing, lightweight, high molecular orientation, and high flexibility in surface functionality, as well as almost unlimited use of biobased and synthetic polymers and blends of various particles [85].…”
Section: Electrospinningmentioning
confidence: 99%
“…However, research on flexible photovoltaic cells is increasingly reported in the literature. The most common flexible substrates used in photovoltaics are made of polymers such as polyethylene naphthalate (PEN) or polyethylene terephthalate (PET) [ 22 , 23 , 25 , 26 , 27 , 28 , 29 ]. Subsequently, polymers are used as materials responsible for forming the porous structure of a semiconducting oxide layer, e.g., TiO 2 .…”
Section: Introductionmentioning
confidence: 99%